2018
DOI: 10.1158/1078-0432.ccr-17-3196
|View full text |Cite
|
Sign up to set email alerts
|

Complete Remission with Reduction of High-Risk Clones following Haploidentical NK-Cell Therapy against MDS and AML

Abstract: Experimental design: Sixteen patients received fludarabine/cyclophosphamide conditioning 68 combined with total lymphoid irradiation followed by adoptive immunotherapy with IL-2-69 activated haploidentical NK cells. 70

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
129
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 43 publications
8
129
0
3
Order By: Relevance
“…In poor prognosis acute myeloid leukemia (AML) patients, NK cell infusions in combination with high dose chemotherapy and IL2 infusion resulted in in vivo expansion of NK cells and complete hematologic remission in 5 out of 19 patients (102). Similar results were more recently shown in elderly high risk AML patients (103), and in high-risk myelodysplastic syndrome (MDS), and again in AML patients (104), where alloreactive NK cells were found in the periphery of all patients and in the bone marrow of some. In neuroblastoma, high doses of NK cell infusions followed by anti-GD2 immunotherapy improved progression free survival, and patient NK cells had increased NKG2A expression (105).…”
Section: Nk Cell Immunotherapysupporting
confidence: 56%
“…In poor prognosis acute myeloid leukemia (AML) patients, NK cell infusions in combination with high dose chemotherapy and IL2 infusion resulted in in vivo expansion of NK cells and complete hematologic remission in 5 out of 19 patients (102). Similar results were more recently shown in elderly high risk AML patients (103), and in high-risk myelodysplastic syndrome (MDS), and again in AML patients (104), where alloreactive NK cells were found in the periphery of all patients and in the bone marrow of some. In neuroblastoma, high doses of NK cell infusions followed by anti-GD2 immunotherapy improved progression free survival, and patient NK cells had increased NKG2A expression (105).…”
Section: Nk Cell Immunotherapysupporting
confidence: 56%
“…Clinical evidence for this hypothesis comes from clinical trials conducted by several independent groups, which showed that NK cell transfusion may induce complete remissions in patients with high-risk acute myeloid leukemia (AML). [1][2][3][4][5] Furthermore, several groups reported associations apply to specific transplant settings: In the setting of HLA class I mismatched HCT, the missing-self hypothesis provides a consistent explanation for NK-cell activation. If inhibitory KIRs do not encounter their cognate ligands on target cells, NK cells may become activated and kill their targets.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 6 refractory patients became eligible for HSCT, suggesting the NK cell therapy may act as a bridge to transplant in otherwise refractory patients. [97] Trials currently enrolling with NK cells are shown in table 1. Chimeric-antigen receptor (CAR) T cells work similarly to NK cell therapy in that they both are endogenous immune regulators coopted to target malignant clones.…”
Section: Introductionmentioning
confidence: 99%